HIF-1alpha and infectious diseases: a new frontier for the development of new therapies - Santos, Sânia Alves dos; Andrade Júnior, Dahir Ramos de (Revista do Instituto de Medicina Tropical de São Paulo, 2017)
The aim of this review is to show the significant role of HIF-1alpha in inflammatory and infectious diseases. Hypoxia is a physiological characteristic of a wide range of diseases from cancer to infection. Cellular hypoxia is sensed by oxygen-sensitive hydrolase enzymes, which control the protein stability of hypoxia-inducible factor alpha 1 (HIF-1alpha) transcription factors. When stabilized, HIF-1alpha binds with its cofactors to HIF-responsive elements (HREs) in the promoters of target genes to organize a broad ranging transcriptional program in response to the hypoxic environment. HIF-1alpha also plays a regulatory function in response to a diversity of molecular signals of infection and inflammation even under normoxic conditions. HIF-1alpha is stimulated by pro-inflammatory cytokines, growth factors and a wide range of infections. Its induction is a general element of the host response to infection. In this review, we also discuss recent advances in knowledge on HIF-1alpha and inflammatory responses, as well as its direct influence in infectious diseases caused by bacteria, virus, protozoan parasites and fungi.